Rakku's story : structures of ill-health and the source of change - Zurbrigg, Sheila (Madras : Published by George Joseph on behalf of the author ; Bangalore : Available from Centre for Social Action, 1984)
Causes of rural ill-health in India; based on the authorʼs experiences in Tamil Nadu.
Bibliography: p. 232-234.
Keywords: Rural health -- India -- Tamil Nadu; Women -- Health and hygiene -- India -- Tamil Nadu; Medical care -- India; Public health -- India; Social medicine -- India